KEWENANGAN MAJELIS PENGAWAS NOTARIS DALAM MELAKSANAKAN PEMBINAAN DAN PENGAWASAN TERHADAP NOTARIS DI SULAWESI BARAT - Sulastri Yasim; Asrullah; Ika Novitasari; Sulaeman; S. Muchtadin Al Attas (Program Studi Hukum Universitas Sulawesi Barat, 2023)
This study aims to determine the authority of the Notary Supervisory Board in carrying out the task of coaching and supervision in West Sulawesi Province. This research applied normative juridical research method by using a statutory approach (statute approach), conceptual approach (conceptual approach), and analytical approach (analytical approach). The results of the study show that the Authority of the Notary Supervisory Board is to supervise, regulate, and protect public interests related to the Notary profession which includes supervision, enforcement ethics, dispute resolution, and maintaining integrity and professionalism in notary practice, especially in West Sulawesi.